2015
DOI: 10.4103/0975-962x.168518
|View full text |Cite
|
Sign up to set email alerts
|

Patients awareness and attitude towards dental implants

Abstract: Aims:The aim of the study was to assess the awareness of the patients regarding implant-retained prosthesis as an option for tooth replacement and the knowledge about tooth replacement as a whole including source of information and attitude towards it amongst Malaysian population.Materials and Methods:Information on demographic characteristics, knowledge about implant as an option for missing tooth replacement, source of information and knowledge about other options of tooth replacement were obtained from pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
36
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 16 publications
13
36
2
2
Order By: Relevance
“…It was observed that the majority (87.9%) of the respondents had heard about the implants. When these results were compared with other studies, similar findings were observed in the studies done by Saha et al, 8 Kohli et al, 9 and Narayanan et al, 13 but these results were not in accordance with the studies done by Raju et al, 14 Sohail et al, 15 Al-Johany et al, 16 Khosya and Devaraj, 5 and Santhosh Kumar et al 17 In this study, participants were not well informed regarding the alternatives of replacement of missing teeth. Participants were only aware about complete denture as an alternative of replacement of missing teeth.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…It was observed that the majority (87.9%) of the respondents had heard about the implants. When these results were compared with other studies, similar findings were observed in the studies done by Saha et al, 8 Kohli et al, 9 and Narayanan et al, 13 but these results were not in accordance with the studies done by Raju et al, 14 Sohail et al, 15 Al-Johany et al, 16 Khosya and Devaraj, 5 and Santhosh Kumar et al 17 In this study, participants were not well informed regarding the alternatives of replacement of missing teeth. Participants were only aware about complete denture as an alternative of replacement of missing teeth.…”
Section: Discussionsupporting
confidence: 79%
“…Figure 1 depicts the survey form which included selfexplanatory questions in correspondence to previous studies conducted by Chowdhary et al, 10 Berge, 12 and Kohli et al 9 A random sampling method with convenient sample size was used. Questionnaire was prepared both in English and Hindi (local language) to improve the participants' understanding of the questions.…”
Section: Ethical Clearance and Official Permissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mc Kenna et al 2016 [18] concluded that previous implant treatment experience and increased income levels were found to strongly influence willingness to pay for implant treatment. Dental Implant treatment was found to be expensive and unaffordable by patients in Malaysia as reported by a survey by Kohli S et al 2015 [17] . In the present study a statistically significant difference (p=0.045) was seen in the oral hygiene status of participants willing for implant treatment when compared to those not willing.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies also assessed the awareness of general population about the pros and cons of implant treatment, financial implications of the procedure, patient expectations and preference of fixed implant treatment over removable prostheses [14][15][16][17][18] . All these studies categorically stated that income levels of the patient is a determining factor in choosing implant treatment, that majority of information gathered by patients is through media and high cost of implants is a major factor that precluded patient preference for the treatment modality.…”
Section: Introductionmentioning
confidence: 99%